Association Between Cardio-Ankle Vascular Index and Early Detection of Heart Failure with Preserved Ejection Fraction: A Meta-Analysis - Pramuliansyah Haq; Andi Muhammad Ariansyah N (International Medical Journal Corp. Ltd, 2026)
Introduction: Heart failure with preserved ejection fraction (HFpEF) represents a growing clinical challenge with limited diagnostic tools for early detection. The Cardio-Ankle Vascular Index (CAVI) is a novel non-invasive measure of arterial stiffness that may facilitate early identification of HFpEF. Methods: This meta-analysis systematically reviewed 48 sources examining the association between CAVI and HFpEF. Studies were included if they assessed adult populations, measured CAVI, and reported quantitative associations with HFpEF or its surrogates. Data extraction focused on study design, CAVI measurement protocols, HFpEF definitions, and association measures. Results: Cross-sectional analyses demonstrated significant correlations between CAVI and diastolic function parameters: E/A ratio (r = -0.405, 95% CI -0.324 to -0.481) and e' velocity (r = -0.449, 95% CI -0.340 to -0.630) (1). CAVI ≥10 was associated with HFpEF hospitalization (OR 9.76) (6). Meta-analyses showed CAVI predicted cardiovascular events (HR 1.20-1.46 per SD/category increase) (8-10). Longitudinal data demonstrated CAVI progression correlated with left ventricular global longitudinal strain deterioration over 26.8 months (5). Sex-specific analysis revealed stronger associations in women (OR 1.67, P=0.007) (3). Discussion: CAVI demonstrates consistent associations with subclinical diastolic dysfunction and HFpEF outcomes. The evidence supports mechanistic plausibility through ventricular-vascular coupling, with distinct patterns in hypertensive and female subpopulations. However, significant limitations include predominance of Asian populations, absence of prospective screening studies, and lack of validated early detection thresholds. Conclusion: CAVI shows promise as a screening tool for early HFpEF detection, particularly in high-risk populations. Future research requires prospective studies with standardized protocols, population-specific thresholds, and evaluation of CAVI-guided intervention strategies.